Enhanced Electrokinetic Transport of Sulfate in Saline Soil - Jo, SungUng; Shin, Yeon-Jun; Yang, Jung-Seok; Moon, Deok Hyun; Koutsospyros, Agamemnon; Baek, Kitae (Kluwer Academic Publishers, 2015)
The electrokinetic transport of sulfate was investigated as a means of treating and restoring a sulfate-accumulating saline soil. The electrokinetic treatment decreased the electrical conductivity of the soil, an indicator of soil salinity, to 58.6, 73.1, and 83.5 % for 7, 14, and 21 days, respectively. More than 96 % of the chloride and nitrate were removed within 7 days. However, the removal of sulfate was highly influenced by the anode material. An iron anode removed sulfate effectively, whereas sulfate was hyper-accumulated in the anodic region when an inert anode was used. The iron anode was oxidized in a sacrificial anodic reaction, which competed with the electrolysis reaction of water at the anode, and finally, the reaction prevented the severe acidification of the soil in the anodic region. However, the competing reactions produced hydrogen ions at the anode and the ions were transported toward the cathode, which, in turn, acidified the soil, especially in the anodic region. The acidification switched the surface charge of the soil from negative to positive, increasing the interaction between the soil surface and sulfate and thus inhibiting the transport of sulfate under the electric field. The zeta potential analysis of the soil provided an explanation. The results indicate that preventing severe acidification is an important factor which influences the transport of anions and iron anode for the enhanced removal of anionic pollutants by electrokinetic remediation.
Keywords: CONTAMINATED PADDY SOIL; ELECTRODE CONFIGURATION; GREENHOUSE SOIL; FOREST SOIL; FIELD APPLICATION; REMEDIATION; RESTORATION; REMOVAL; ADSORPTION; PB